Criteria of Sharī‘ah supervisory committee: a comparative study between guidelines of Bangladesh Bank and Bank Negara Malaysia - Amanullah, Muhammad (IIUM Press, 2015)
Islamic banking and finance differs from conventional banking and finance in that it follows the rules of Sharī‘ah. In order to ensure that Islamic banking and finance follows the Sharī‘ah rulings, it is essential for it to have a Sharī‘ah supervisory board. An important duty of this board is to determine that the products, services, policies, guidelines and all other activities performed by the Islamic bank, are in compliance with the Sharī‘ah rulings. To perform their duty properly, the members of this board should possess certain criteria. Bangladesh Bank has spelled out some guidelines for these criteria briefly. Likewise, Bank Negara Malaysia has provided some guidelines. The main objectives of this research paper are to highlight the guidelines of these two banks on these criteria, compare them and evaluate them in light of Sharī‘ah guidelines on these criteria spelled out by contemporary Muslim jurists.